The Benefits of Acupuncture Combined with a Low Purine Diet to Improve Uric Acid and Total Cholesterol in Diabetes Mellitus Patients with Hyperuricemia - Sumanto Sumanto; Joko Tri Haryanto; Heni Nur Kusumawati (Masters Program in Public Health, 2022)
Background: Diabetes mellitus with hyperuricemia causes the accumulation of monosodium urate crystals in the synovial joint tissue. The incidence of gout in Indonesia according to the Indonesian Rheumatology Association, namely: gout 1-2 percent of adults, is the most cases of arthritis in men and is estimated to be between 13.6 per 1,000 men and 6.4 per 1,000 women. The prevalence of gout increased with age, an average of 7 percent of men >75 years and 3 percent of women >85 years.Subjects dan Method: Quasi-Experimental with pre and post-test designs. The research time is between March to September 2021 at the Posyandu for the elderly in Surakarta City. The population of this study were all objects with fasting blood sugar levels between 100 mg/dl - 125 mg/dl and above 126 mg/dl, female blood uric acid levels exceeding 5.6 mg/dl in men and exceeding 6.5 in the city. Surakarta, sample selection using purposive sampling, sample size 40 subjects. The dependent variable is uric acid, cholesterol and total blood levels, the independent variable is combination acupuncture therapy with a low purine diet. The research instrument used a checklist for blood analysis and physical examination. Data analysis using t-test.Results: Uric acid levels after acupuncture therapy in the intervention group were lower (Mean= 3.31; SD= 0.61) than the control group (Mean= 5.83; SD= 1.29), and not statistically significant (p= 0.935). Total cholesterol level after acupuncture therapy in the intervention group was lower (Mean= 166.00; SD= 34.20) than the control group (Mean= 222.30; SD= 55.43), but it was statistically non-significant (p= 0.676).Conclusion: Acupuncture therapy can reduce uric acid levels and total cholesterol levels. Keywords: Acupuncture, low purine diet, uric acid level, cholesterol level Correspondence:Sumanto. College Leading Basic Research, Acupuncture Course, Health Polyetchnics, Ministry of Health Surakarta. Jl. Letjend Sutoyo Mojosongo, Surakarta, Central Java. Email: sumantoiman@gmail.com. Mobile phone: 08121608067.